Evaluation of immunological parameters in pit bull terrier‐type dogs with juvenile onset generalized demodicosis and age‐matched healthy pit bull terrier‐type dogs. Issue 6 (23rd August 2018) - Souza, Clarissa P.; Schissler, Jennifer R.; Contreras, Elena T.; Dow, Steven W.; Hopkins, Leone S.; Coy, Jonathan W.; Rosychuk, Rod A.W.; Hawley, Jennifer R.; Lappin, Michael R.
Abstract : Background: Juvenile onset generalized demodicosis (JOGD) is thought to occur due to immunological abnormalities and is over‐represented in pit bull terrier‐type dogs. Animals: Twelve pit bull terrier‐type dogs with JOGD and 12 age‐matched healthy pit bull terrier‐type dogs. Objective: To investigate immunological differences between age‐matched healthy and JOGD pit bull terrier‐type dogs by flow cytometry, multiplex, molecular and serological assays. Methods and materials: Flow cytometry quantified B cells expressing MHCII or surface‐bound IgG, CD4+ T cells expressing MHCII, CD8 T cells expressing MHCII or CD11a, neutrophil and monocyte markers. Surface expression was quantified by calculating the geometric mean fluorescence index. The Wilcoxon rank sum test was used to compare median results for IL‐2, IL‐4, IL‐6, IL‐7, IL‐8, IL‐10, IL‐13, IL‐18, FOXP3, monocyte chemoattractant protein‐1, GM‐CSF, KC, IgE, IgA, IgG, IgM, C‐reactive protein, lymphocyte, neutrophil and monocyte in the groups. IFN‐gamma, IP‐10, IL‐15, IL‐31 and TNF‐alpha also were measured; however, insufficient dogs (<5) had values that were in range of the assay to allow for statistical evaluation. Significance was defined as P  < 0.05. Results: Serum concentrations of IL‐2, IL‐18 and MCP‐1 were significantly higher ( P  = 0.01, P  = 0.01, P  = 0.04) in the JOGD group. Also, IgA median value was significantly higher ( P  = 0.002) in pit bull terrier‐type dogs with JOGD. Flow cytometry revealed that T‐cell, neutrophil and monocyte markers were not different between groups. Conclusions: Results suggest an appropriate compensatory immune response by pit bull terrier‐type dogs in the JOGD group and do not support the explanation of global immune deficiency in these dogs. Abstract : Background – Juvenile onset generalized demodicosis (JOGD) is thought to occur due to immunological abnormalities and is over represented in pit bull terrier‐type dogs.Objective – To investigate immunological differences between age‐matched healthy and JOGD pit bull terrier‐type dogs by flow cytometry, multiplex, molecular and serological assays.Conclusions – Results suggest an appropriate compensatory immune response by pit bull terrier‐type dogs in the JOGD group and do not support the explanation of global immune deficiency in these dogs.